(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Recent research on human resource management (HRM) has highly debated concerns and issues in the regard to the development of technology over the past decades, from e-data to HR specialists (Kim, Wang & Boon, 2021). Nowadays, the term ‘Algorithmic Human Resource Management’ is used to be internal data collection of digital technology in HRM. Algorithmic HRM refers to ‘the use of software that works based on digital data to enhance HR-related decisions and/or systematize HRM actions’ (Meijerink, Boons, Keegan & Marler, 2021).